El profesor como fuente de motivación de los estudiantes: Hablando del qué y del por qué del aprendizaje de los estudiantes - Lens, Willy (2015)
In this article we will discuss how teachers, principals, student counselors, and other professionals in education, can enhance the quantity and the quality of students' motivation by affecting what students are motivated for (i.e., their academic achievement goals) and the reasons why they strive to reach those goals. Based on Achievement goal theory and on Selfdetermination theory we will discuss these qualitative differences in students' motivation and we will explain why teachers should create a learning environment that fosters these more optimal types of motivation.